Assessment of WHO antibiotic consumption and access targets in 76 countries, 2000–15: an analysis of pharmaceutical sales data - Klein, Eili Y; Milkowska-Shibata, Maja; Tseng, Katie K; Sharland, Mike; Gandra, Sumanth; Pulcini, Céline; Laxminarayan, Ramanan (The Lancet infectious diseases, 2021)
The WHO Access, Watch, and Reserve (AWaRe) antibiotic classification framework aims to balance appropriate access to antibiotics and stewardship. We aimed to identify how patterns of antibiotic consumption in each of the AWaRe categories changed across countries over 15 years. Antibiotic consumption was classified into Access, Watch, and Reserve categories for 76 countries between 2000, and 2015, using quarterly national sample survey data obtained from IQVIA. We measured the proportion of antibiotic use in each category, and calculated the ratio of Access antibiotics to Watch antibiotics (access-to-watch index), for each country. Between 2000, and 2015, global per-capita consumption of Watch antibiotics increased by 90·9% (from 3·3 to 6·3 defined daily doses per 1000 inhabitants per day [DIDs]) compared with an increase of 26·2% (from 8·4 to 10·6 DIDs) in Access antibiotics. The increase in Watch antibiotic consumption was greater in low-income and middle-income countries (LMICs; 165·0%; from 2·0 to 5·3 DIDs) than in high-income countries (HICs; 27·9%; from 6·1 to 7·8 DIDs). The access-to-watch index decreased by 38·5% over the study period globally (from 2·6 to 1·6); 46·7% decrease in LMICs (from 3·0 to 1·6) and 16·7% decrease in HICs (from 1·8 to 1·5), and 37 (90%) of 41 LMICs had a decrease in their relative access-to-watch consumption. The proportion of countries in which Access antibiotics represented at least 60% of their total antibiotic consumption (the WHO national-level target) decreased from 50 (76%) of 66 countries in 2000, to 42 (55%) of 76 countries in 2015. Rapid increases in Watch antibiotic consumption, particularly in LMICs, reflect challenges in antibiotic stewardship. Without policy changes, the WHO national-level target of at least 60% of total antibiotic consumption being in the Access category by 2023, will be difficult to achieve. The AWaRe framework is an important measure of the effort to combat antimicrobial resistance and to ensure equal access to effective antibiotics between countries. US Centers for Disease Control and Prevention.